IF YOU WANT TO BE HEALTHY!!! - Rozikova Mohira Odinayevna (Scholar Express Journals, 2022)
Although modern medicine has made significant progress in treating many diseases, it often turns out to be weak when the human body is unable to fight the disease even with the help of drugs and medical interventions. To prevent this, we need to know and follow specific prevention methods and rules that are the basis of a healthy lifestyle
Keywords: Healthy; Lifestyle; Human Body; medicine